Isolation of Mycobacterium frederiksbergense From Redundant Tap Water: A Case Report - Masoud Keikha (Hamadan University of Medical Sciences, 2017)
Non-tuberculosis mycobacteria (NTM) are saprophytic bacteria in environmental resources such as water and soil. The presence of atypical mycobacteria in hospital resources may lead to infections and the spread of aerosol particles through ventilation systems, wind, and even drinking water. Therefore, control of contamination of environmental resources in hospitals is one of the most important approaches to reduce and manage NTM nosocomial infections. This study reported the isolation of Mycobacterium frederiksbergense from a tap water sample, which is considered important for clinical and biodegradation aspects. The isolated bacterium was identified using phenotypic features and 16S rRNA sequencing. This report verified the necessity to identify the presence of NTM in water and to find a solution for controlling such contaminations.